Impact of proprioception during the oral phase on initiating the swallowing reflex. (15th September 2015) - Takeda, Hikaru; Saitoh, Kazuya
Abstract : Objectives/Hypothesis: We hypothesized that proprioceptive signals during the oral phase play a pivotal role in the initiation of pharyngeal phase during volitional swallowing. Therefore, we tested if swallowing could be modified by changing the amount of proprioceptive feedback from a number of different receptors while holding a food bolus in the mouth and clenching. Study Design: Basic research. Methods: Surface electromyography (sEMG) recordings of the masticatory muscles were obtained during volitional swallowing movements from seven healthy adults with no clinical history of swallowing difficulties. The swallowing procedure involved holding 5 ml of jelly on the tongue before swallowing it completely, according to visual cues on a computer display. Initiation of the swallowing reflex was detected by an anterior shift of the thyroid cartilage using a laser displacement sensor and by submental sEMG signals. To vary the proprioceptive input, the participants were instructed to occlude their teeth at various intensities (weak, intermediate, and strong) while holding the 5‐ml jelly bolus on the tongue. Results: Rectified and integrated sEMG (iEMG) signals obtained from the submental area showed two upward deflections. Contractile forces of the masseter muscles showed significant negative values for Pearson correlation coefficient against time intervals from the onset of the second submental iEMG deflection to the onset of the anterior shift of the thyroid cartilage in six of the seven participants (average −0.534, standard deviation 0.176). Conclusion: Contractile forces of the masseter muscles during occlusion tended to correlate negatively with electromechanical delays on suprahyoid muscle contraction. Level of Evidence: NA Laryngoscope, 126:1595–1599, 2016